Non-pharmacological interventions to reduce vaccination-related pain in infants: an integrative review - Lílian Maria Almeida Costa; Rosana dos Santos Costa; Magda Coeli Vitorino Sales; Márcia Teles de Oliveira Gouveia; Mayara Águida Porfírio Moura (Programa de Pós Graduação em Enfermagem da Universidade Federal do Piauí, 2023)
Objective: To identify scientific evidence related to non-pharmacological interventions used to reduce vaccination-related pain in infants. Methods: This is an integrative review carried out using the PICo strategy, in the IBECS, MEDLINE and Scopus databases, from February to June 2022, which aimed to answer the following question: what is the scientific evidence regarding non-pharmacological interventions used to reduce pain associated with vaccination in infants? The descriptors combined with the OR and AND Booleans were infant, vaccination, pain. Articles from 2011 to 2021 and published in Portuguese, English or Spanish were included. Results: The final sample consisted of 32 studies. Non-pharmacological intervention measures proposed for pain relief in infants submitted to vaccination were: breastfeeding and oral sugar solutions; professional assistance in the vaccine room; and sensory stimulation measures. Conclusion: Using these strategies evidenced in the scientific literature is able to favor the most adequate management of pain related to vaccine administration and, therefore, increase infants' comfort and well-being, in addition to favoring families' compliance with vaccination.